Scientific basis for the trainer aircraft anti-g equipment requirements - M. A. Kiselev; S. V. Levitsky; D. V. Moroshkin (Научный вестник МГТУ ГА)
The design process of a new aircraft (AC) is always associated with the issue of choosing its basic technical parameters, or, in other words, the formation of its conceptual design. In case of a civil aircraft, the choice of these parameters is defined by the requirements for operational safety, market conditions, norms that specify the tolerable harmful impact of the aircraft on the environment, etc. In case of a military aircraft, its outlay mostly depends on the concept of potential military threats, ways of using the military aircraft in military conflicts. Some of these requirements are formulated in regulatory documents – the Aviation Requirements for Civil Aircraft and the General Tactical and Technical Requirements of the Air Force for Military Aircraft. For example, Part 25 of the Aviation Requirements for Civil Aircraft defines the Airworthiness Standards for transport aircraft. It should be noted that the stated above requirements are often a tool of competition, for example, when tightening the aircraft noise abatement procedures provides advantages for particular manufacturers, not admitting other manufacturers to enter the market, whose aircraft do not conform to the new standards. Thus, complying with the requirements virtually involves additional costs both in the aircraft development and during its operation. In addition, the implementation of the requirements stated above can lead to the deterioration of the aircraft’s performance, and hence, to the decrease of its competiveness and combat effectiveness. Therefore, each requirement of the regulatory documents should have a profound scientific rationale. This article analyzes one of the regulatory documents requirements referring to the necessity of anti-g system on board aircraft. The authors propose the approach to specify the existing criterion to provide the scientific basis for the anti-g system on board aircraft by assessing the actual level of pilot load when maneuvering. The subject under study is of particular importance for the Yak-152 trainer aircraft. The actual level of loads during pilotage of the Yak-152 trainer aircraft does not require the use of the anti-g system but if to be based on a formal criterion, namely, in terms of the maximum operational overload value, the aircraft should be fitted out with such a system.